PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU PENCEMARAN NAMA BAIK MELALUI MEDIA SOSIAL (STUDI KASUS TERHADAP PUTUSAN PERKARA NOMOR : 432/PID.SUS/2019/PN.BNA). - Husnatika Ayyasy (2022)
The freedom to express thoughts and opinions orally and in writing belongs to all Indonesian people. Indonesia recognizes that expressing thoughts and opinions orally and in writing, freedom of expression and freedom of the press are basic rights that must be enjoyed by all levels of the people, but the fact is that these freedoms have not been fully granted to all people. Decisions that contain the truth, are impartial, can be accounted for and treat every human being on the same position before the law are justice. The writing of this scientific paper uses a normative legal research method with a statute approach and a case approach. This study aims to determine criminal liability for defamation through social media (Case Study Decision Case Number: 432/Pid.Sus/2019/PN.Bna) and analyze the judge's legal considerations in deciding criminal cases of Defamation through Social Media. Based on the decision number 432/Pid.Sus/2019/Pn.Bna, the Defendant Saiful Mahdi was found guilty of Defamation of Taufiq Saidi but based on the Defendant's research, Saiful Mahdi only criticized a CPNS acceptance system. This makes the implementation of the ITE Law often considered a rubber article and silences freedom of expression.